Children of the mind - Card, Orson Scott (TOR science fiction., 2021)
"The planet Lusitania is home to three sentient species: the pequeninos, a large colony of humans, and the hive queen, brought there by Ender Wiggin. But now, once again, the human race has grown fearful: the Starways Congress has gathered a fleet to destroy Lusitania. Ender's oldest friend, Jane, an evolved computer intelligence, can save the three sentient races of Lusitania. She has learned how to move ships outside the universe, and then instantly back to a different world, abolishing the light-speed limit. But it takes all the processing power available to her, and the Starways Congress is shutting down the network of computers in which she lives, world by world. Soon Jane will not be able to save the ships. Ender's children must save her if they are to save themselves."--